2012
DOI: 10.1007/s11627-012-9443-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of l-phenylalanine on PAL activity and production of naphthoquinone pigments in suspension cultures of Arnebia euchroma (Royle) Johnst

Abstract: The effects of l-phenylalanine (PHE) on cell growth and production of shikonin and its derivatives, acetylshikonin (ACS) and isobutyrylshikonin (IBS), in suspension cultures of Arnebia euchroma were examined. Supplementing media using PHE have been successfully utilized to enhance shikonin production in cell cultures of other species of Boraginaceae. l-Phenylalanine, the key compound in the phenylpropanoid pathway, is converted by phenylalanine ammonia lyase (PAL) to trans-cinnamic acid, which is the precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
3
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 29 publications
0
40
3
5
Order By: Relevance
“…Two peaks of PAL activity were observed for Salvia miltiorrhiza cells (Dong et al 2010) with elicitor induction time, but the first one coincided with the peak of a phenolic compound while the second one coincided with the shikonin peak. However, there was no direct correlation between the peaks of PAL activity and the shikonin production peak under L-phenylalanine treatments in Arnebia euchroma (Sykłowska-Baranek et al 2012). In our study, the peak of PAL activity was observed at 25 mM (low dose), 150 and 175 mM (high dose) NaCl treatments and coincided with the peak of flavonoid production (Table 1), while the lower PAL activity and flavonoid content was observed at 75 mM NaCl.…”
Section: Discussioncontrasting
confidence: 68%
“…Two peaks of PAL activity were observed for Salvia miltiorrhiza cells (Dong et al 2010) with elicitor induction time, but the first one coincided with the peak of a phenolic compound while the second one coincided with the shikonin peak. However, there was no direct correlation between the peaks of PAL activity and the shikonin production peak under L-phenylalanine treatments in Arnebia euchroma (Sykłowska-Baranek et al 2012). In our study, the peak of PAL activity was observed at 25 mM (low dose), 150 and 175 mM (high dose) NaCl treatments and coincided with the peak of flavonoid production (Table 1), while the lower PAL activity and flavonoid content was observed at 75 mM NaCl.…”
Section: Discussioncontrasting
confidence: 68%
“…It exhibits biological activities such as wound healing (Yin et al 2013), antioxidant (Weng et al 2000), antifungal and antitumour (Han et al 2008;Yang et al 2009;Lu et al 2011;Andujar et al 2013). Previous phytochemical studies reported that the red pigments of L. erythrorhizon were mainly composed of naphthoquinone compounds, such as b-hydroxyisovalerylshikonin, acetylshikonin (Gwon et al 2012), propionylshikonin (Cho et al 1999), isobutyrylshikonin (Syklowska-Baranek et al 2012), b,b-dimethylacryloylshikonin (Li et al 2012, isovalerylshikonin, isobutyrylshikonin (Zhao et al 2011) and a-methylbutyrylshikonin.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Baranek et al showed that shikonin had positive effects on inhibition of cells. 18 Haghbeen et al prepared 2 different cultures for A. euchroma which had high amounts of pigments. However, antimicrobial experiments showed that they had no effects on gram-negative bacteria and fungi, but optimal effects were observed on gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%